(untitled) (RPG学研究: Japanese Journal of Analog Role-Playing Game Studies, 2024)
Table-talk Role-Playing Games (TRPGs) combine both storytelling and gameplay elements. Storytelling involves role-playing (acting in character), and some systems incorporate rules that encourage role-playing. This paper begins by reviewing the evolution of experience point systems in representative TRPG systems. Shinobigami, a ninja battle RPG, was selected as the primary research subject due to its innovative implementation of unprecedented rules. The key features of Shinobigami include a high degree of freedom in PC (player character) selection to meet diverse player needs, a scene system that ensures fair participation opportunities, and an experience point system that actively identifies and rewards positive traits. Among the various mechanics, this study investigates the effectiveness of the “Touched the Heartstrings” rule, where players vote for each other as part of the design of incentives. Based on the 2023 sales figures, Shinobigami appears effective in binding its users, suggesting that the game has become a popular and classic TRPG many players enjoy.